2012
DOI: 10.4236/health.2012.49094
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding preventive measures of heart disease among the adult population in Kathmandu

Abstract: Heart disease is the leading cause of death globally. Prevention is the most effective way of combating its epidemic in the resource poor nations. Knowledge on preventive measures of heart diseases has been identified as a prerequisite for change in behavior. This study was conducted with the purpose of identifying the knowledge on heart disease and its prevention among the adults population residing in Dadhikot VDC of Bhaktapur district by interviewing house to house survey. A total of 405 respondents who met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
2
5
0
1
Order By: Relevance
“…Another study conducted by (Pandey & Khadka, 2012) in Kathmandu showed that age, family history was recognized was 46.9 % and 39.8% of study participants respectively which is similar with the finding of this study. However, sex was recognized by only 13.8 % of respondents which showed distinction with the finding of this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Another study conducted by (Pandey & Khadka, 2012) in Kathmandu showed that age, family history was recognized was 46.9 % and 39.8% of study participants respectively which is similar with the finding of this study. However, sex was recognized by only 13.8 % of respondents which showed distinction with the finding of this study.…”
Section: Discussionsupporting
confidence: 82%
“…In this study decreasing fatty food consumption, eating fruits and vegetables was most recognized by the respondents as the ways to prevent CHD which is similar to the study conducted by (Pandey & Khadka, 2012).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…(9) Karşılaştırmalı bir çalışmada da, tip 2 diyabetli bireylerin diyabeti olmayan bireylere göre risk bilgilerinin daha düşük olduğu, ancak her iki grup arasında anlamlı fark olmadığı saptanmıştır. (12) Toplumun kardiyovasküler hastalıklar risk faktörlerine yönelik bilgi düzeylerinin incelendiği çalışmalarda ise, katılımcıların orta (29,(31)(32)(33) ya da iyi düzeyde bilgiye sahip oldukları belirlenmiştir. (34) Çalışma bulgusu, bireylerin kardiyovasküler hastalıkların önlenmesinde ve tedavisinde kısmen bilgi sahibi olduklarını göstermesi açısından olumlu olarak değerlendirilmektedir.…”
Section: Verilerin Değerlendirilmesiunclassified
“…Creating awareness about these risk factors and spreading knowledge about their prevention should be the main target of health education programs. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%